Application of QuEChERS Method for Simultaneous Determination of Pesticide Residues and PAHs in Fresh Herbs - Sadowska-Rociek, Anna (Springer-Verlag, 2013)
The aim of this study was to evaluate the application of quick, easy, cheap, effective, rugged and safe method for simultaneous determination of polycyclic aromatic hydrocarbons and pesticide residues in fresh herbs. In the experiment two extraction solvents and standard types of sorbents were used. The extracts were analyzed using GC–SIM–MS. The results suggest that acetonitrile is more suitable extraction solvent giving more purified samples and better recovery values (71.6 %–116.9 %) with RSD lower than 15 % for most of the compounds. In real samples pesticides were identified in the samples of parsley, tarragon and lovage. In few samples the pesticide levels exceeded the MRL established by EU.